2009
DOI: 10.1097/fbp.0b013e3283242f05
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of dopamine receptors and drug addiction: a comprehensive review

Abstract: Drug dependence is a chronic, relapsing disorder in which compulsive drug-seeking and drug-taking behaviours persist despite serious negative consequences. Addictive substances, such as opioids, ethanol, psychostimulants and nicotine, induce pleasant states or relieve distress, effects that contribute to their recreational use. Dopamine is critically involved in drug addiction processes. However, the role of the various dopaminergic receptor subtypes has been difficult to delineate. Here, we will review the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
218
0
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(228 citation statements)
references
References 288 publications
1
218
0
9
Order By: Relevance
“…The fact that there is an increase of DA transmission at the level of D 3 receptors give further validity to the hypothesis that blocking DA transmission at the level of D 3 could be an effective strategy for nicotine addiction (Khaled et al, 2010;Le Foll et al, 2007). Further studies should explore the role of the ventral pallidum in drug addiction (Kemppainen et al, 2012) and notably the role of the D 3 receptors (Le Foll et al, 2009a;Tziortzi et al, 2011) in this area.…”
Section: (C) Expectancy Factor (Tobacco Craving Questionnaire Tcq)mentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that there is an increase of DA transmission at the level of D 3 receptors give further validity to the hypothesis that blocking DA transmission at the level of D 3 could be an effective strategy for nicotine addiction (Khaled et al, 2010;Le Foll et al, 2007). Further studies should explore the role of the ventral pallidum in drug addiction (Kemppainen et al, 2012) and notably the role of the D 3 receptors (Le Foll et al, 2009a;Tziortzi et al, 2011) in this area.…”
Section: (C) Expectancy Factor (Tobacco Craving Questionnaire Tcq)mentioning
confidence: 99%
“…Elevations in extracellular DA induced by smoking have been associated to either craving (Brody et al, 2006;Brody et al, 2004), improved mood (Barrett et al, 2004;Brody et al, 2009;Montgomery et al, 2007) or greater puff volume (Brody et al, 2010). Therefore, the role of DA in nicotine addiction still remains unclear (refer to the study by Le Foll et al (2009a) for a review). While some authors agree that DA signaling at the D2/3 receptor appears to mediate the rewarding and motivational effects of nicotine, other have argued that DA may instead mediate aversion to acute nicotine or nicotine withdrawal (Grieder et al, 2012;Laviolette and Van Der Kooy, 2003a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Such a finding is not surprising given that these two systems are the most often examined neurotransmitters in all types of addiction disorders [36,37]. In case of dopamine, the role of the brain reward system is most likely to be involved [38], whereas in case of serotonin, the regulation of behavioral inhibition is most likely to be involved [39]. Nevertheless, the available published studies refer exclusively to genetic etiological factors, which are also reported in other types of addictions.…”
Section: Discussionmentioning
confidence: 71%
“…Following these very early studies Blum and Noble and their respective groups reported on the first ever confirmed association of the dopamine D2 receptor gene (DRD2) and severe alcoholism [17]. While the findings were controversial at the time, [18] it is confirmed [19] and remains the most widely studied gene in psychiatric genetics. The discovery lead to the development of an entire field of medicineknown as Psychiatric Genetics and it has 14,937 publications as of 10/26/14 on PubMed.…”
Section: Embracing New Solutions and Genetic Risk Assessmentmentioning
confidence: 87%